PERAN DAN TANGGUNG JAWAB LEMBAGA PELAYANAN PENEMPATAN DAN PERLINDUNGAN PEKERJA MIGRAN DI INDONESIA - Atedjadi, Ribka Lydia (Faculty of Law, Parahyangan Chatolic University, 2015)
Migrant workers are the universal right holders whose rights, dignity and security require special and specific kinds of protection. The international migrant workers happen to find themselves outside of their nationality law protection system, hence their status is absolutely crucial, as they are susceptible to exploitation and harassment. This protection has been provided since the activities of the labor system in the market are related to pre-placement, placement, and post-placement. The actual implementation of this form of protection currently falls under an institution in charge of services and protection. This institution is known in Indonesia as Badan Nasional Penempatan dan Perlindungan Tenaga Kerja Indonesia, the National Institution for the Placement and Protection of Indonesian Laborers (BNPPTKI). The vulnerability of Indonesian migrant laborers can be discerned from a number of issues such as execution of the death penalty in the country of destination without any notification being given to the government of their country of origin, and acts of violence committed against Indonesian migrant workers in their workplace that is quite susceptible to 3D. By way of its various institutions, Indonesia must address the issues of migrant workers seriously and regard this matter as being subject to law in specific situations. The safe and proper migration situation of Indonesian International workers should become a role model and fall under the responsibilities of the placement institutions services and protections in order to minimize the legal issues faced by the Indonesian workers.